-2+8x+5=-10x+3+18x

Simple and best practice solution for -2+8x+5=-10x+3+18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+8x+5=-10x+3+18x equation:



-2+8x+5=-10x+3+18x
We move all terms to the left:
-2+8x+5-(-10x+3+18x)=0
We add all the numbers together, and all the variables
8x-(8x+3)-2+5=0
We add all the numbers together, and all the variables
8x-(8x+3)+3=0
We get rid of parentheses
8x-8x-3+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 4w+50=122 | | 78+6n=42 | | 22=5x−7 | | 4(3x–5)+2x=22 | | 7x-9x=172 | | 16.5=a-5.337 | | 2(n-8)=-2n+4 | | f(6)=34 | | 19/3=6/x | | 3/2=a/8 | | 7x-36=5x+12=180 | | 9y-54=4y+12 | | F(h+1)=(h+1)^2-5(h+1)+8 | | 2(v-1)=14 | | A=-2x^2+24x-3 | | -1x+10=-2(x–1) | | 12x-26=3x+1 | | 3(3b+4)=2(5b+1) | | 5x×3=(-2) | | 6x-136x-13=3x+1 | | 0.96=200/x | | 20=3k-2 | | x-31/8=5/2 | | n+7+2n-5=180 | | 9n=72n | | 5y+77=90 | | 9x^2-6x=-5 | | -1=-16w | | 6x=4=4x-14 | | 60x=5x+5 | | -15-5(6-2y)=-105 | | −3-17x=14 |

Equations solver categories